2017
DOI: 10.1186/s12916-017-0830-8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to bacterial products lipopolysaccharide and flagellin and hepatocellular carcinoma: a nested case-control study

Abstract: BackgroundLeakage of bacterial products across the gut barrier may play a role in liver diseases which often precede the development of liver cancer. However, human studies, particularly from prospective settings, are lacking.MethodsWe used a case-control study design nested within a large prospective cohort to assess the association between circulating levels of anti-lipopolysaccharide (LPS) and anti-flagellin immunoglobulin A (IgA) and G (IgG) (reflecting long-term exposures to LPS and flagellin, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 59 publications
5
42
1
Order By: Relevance
“…that LBP in live cancer cells may engage in the local immune response to gut-derived bacterial translocation, which was an etiological factor of HCC according to current reports (29,30). The association of LBP and clinicopathological parameters was further investigated by analyzing the LIHC cohort from TCGA.…”
Section: The Prognostic Significance Of Lbp Is Dependent On the Hepatmentioning
confidence: 99%
“…that LBP in live cancer cells may engage in the local immune response to gut-derived bacterial translocation, which was an etiological factor of HCC according to current reports (29,30). The association of LBP and clinicopathological parameters was further investigated by analyzing the LIHC cohort from TCGA.…”
Section: The Prognostic Significance Of Lbp Is Dependent On the Hepatmentioning
confidence: 99%
“…Murine studies have reported that exposure to the bacterial products lipopolysaccharide (LPS) and flagellin can cause inflammation and oxidative stress in the liver and may promote HCC (9)(10)(11). Similarly, evidence from human studies suggests that systemic exposure to these bacterial products may be positively associated with systemic inflammation (12,13) and chronic liver disease (14)(15)(16)(17). Thus far, the only study in humans to examine the association between antibodies (IgA and IgG, jointly) to LPS and flagellin and the risk of liver cancer reported a positive association (13).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, evidence from human studies suggests that systemic exposure to these bacterial products may be positively associated with systemic inflammation (12,13) and chronic liver disease (14)(15)(16)(17). Thus far, the only study in humans to examine the association between antibodies (IgA and IgG, jointly) to LPS and flagellin and the risk of liver cancer reported a positive association (13). Whether individual immunoglobins (IgA vs. IgG vs. IgM) were associated with risk, however, has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies suggest that LPS and flagellin blood levels may be correlated with a higher cancer risk (50,51). However, contradictory studies show decreased cell proliferation in LPS-or flagellin-stimulated cells (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%